2016
DOI: 10.1042/bcj20160041
|View full text |Cite
|
Sign up to set email alerts
|

Sticky swinging arm dynamics: studies of an acyl carrier protein domain from the mycolactone polyketide synthase

Abstract: When covalently linked to an acyl carrier protein (ACP) and loaded with acyl substrate-mimics, some 4′-phosphopantetheine prosthetic group arms swing freely, whereas others stick to the protein surface, suggesting a possible mode of interaction with enzyme domains during polyketide biosynthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0
12

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(52 citation statements)
references
References 54 publications
2
38
0
12
Order By: Relevance
“…Unfolding studies of the apo‐ and holo‐forms of Plasmodium falciparum ACP revealed that the holo‐form had greater stability than its apo‐counterpart due to hydrophobic interactions between the protein and the prosthetic group . However, an increase in the melting temperature was also observed for an holo‐ACP form of the mycolactone polyketide synthase from Mycobacterium ulcerans where the phosphopantetheine moiety appeared to swing freely around the highly conserved attachment site . In our study, we also investigated the effect of attached phosphopantetheine on protein stability.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Unfolding studies of the apo‐ and holo‐forms of Plasmodium falciparum ACP revealed that the holo‐form had greater stability than its apo‐counterpart due to hydrophobic interactions between the protein and the prosthetic group . However, an increase in the melting temperature was also observed for an holo‐ACP form of the mycolactone polyketide synthase from Mycobacterium ulcerans where the phosphopantetheine moiety appeared to swing freely around the highly conserved attachment site . In our study, we also investigated the effect of attached phosphopantetheine on protein stability.…”
Section: Discussionmentioning
confidence: 86%
“…40 However, an increase in the melting temperature was also observed for an holo-ACP form of the mycolactone polyketide synthase from Mycobacterium ulcerans where the phosphopantetheine moiety appeared to swing freely around the highly conserved attachment site. 41 In our study, we also investigated the effect of attached phosphopantetheine on protein stability. The DSC data (Table I) indicate a substantial increase in the melting temperature for holo-LipD in the EDTA-chelated form.…”
Section: Discussionmentioning
confidence: 99%
“…Complex polyketides harbor numerous methyl groups possessing L stereochemistry, whereas the KSs of modular PKSs catalyze the generation of (2D)-2-methyl-3-ketoacyl-ACPs exclusively during the elongation of polyketide intermediates (Castonguay et al, 2007; Weissman et al, 1997; Xie et al, 2017). In addition, the binding of the acyl group to a patch on the surface of the ACP prevents the water-catalyzed epimerization observed for the C2 methyl group of the NAC- or pantetheine-bound thioesters (Castonguay et al, 2007; Vance et al, 2016). The EIX assays provide direct evidence that A2- and B2-type KRs have intrinsic epimerase activities.…”
Section: Discussionmentioning
confidence: 99%
“…The experiments described above demonstrate that the interaction between an acyl-ACP species and a KR/cofactor binary complex is multivalent, comprising distinct contributions from the ACP surface, the prosthetic group and the thioester-linked substrate. However, the increase in affinity observed when the Ppant and acyl moieties are included is relatively small, indicating that the entropic penalties engendered by restricting the motion of the freely swinging prosthetic group arm 25 are only just compensated for by the favourable enthalpy change resulting from extension of the binding interface. The net effect is likely to be an increase in the specificity of the interaction (due to contacts with multiple binding sites), but with only minor effects on the dissociation constant.…”
mentioning
confidence: 99%